A Study of E- Commerce and Online Shopping - Vashistha, Rashmi; Kumar, Sudhir (Journal of Commerce and Trade, 2016)
E-commerce and online shopping in India is getting a noticeable growth as more usage of internet facilities, high educational standards, changing life style and economical growth of the country reasons in the demand of ecommerce techniques and tools. Versatile shopping experience and rapid development of transaction facilities is further boosting opportunities for the remaining market segments. The biggest advantage of e-commerce is the ability to provide secure shopping transactions via the internet and coupled with almost instant verification and validation of credit card transactions. One of the most important issues to be addressed in electronic commerce is the area of services. The primary purpose of this study is to examine and uncover the impact of e-commerce and also identify the issues and areas important to the implementation of e-commerce that may help in enhancing the productivity in the economic growth of the country.